Result-based Management Implementation in Higher Education Institution: Determinants and Impact on Performance - Suryo Pratolo; Arifin Hamsyah Mukti; Misbahul Anwar (Journal of Accounting and Investment, 2020)
Abstract:Research aims: This research is purposed to examine human resource quality impact, organizational commitment and reward and punishment system to RbM implementation. More over, this research also examined RbM’s impact to Higher Education Institution (HEI) Performance as well as RbM’s role as variabel intervening.Design/Methodology/Approach: Samples in this research were collected using convenience sampling  method. This research uses survey method. Data in this research shall be primary data. Data collection method was executed by using questionnaire. Partial Least Square (PLS) technique was employed to test hypotheses proposed.Research findings: This research shows Human Resource Quality, Organizational Commitment as well as reward and punishment system are proven having positive and significant impacts to RbM’s implementation. Then RbM’S implementation is proven having impact to HEI Performance. Direct relationship to HEI Performance, Human Resource variable, Organisatonal Commitment, and reward and punishment system are not proven directly on HEI Performance, but specifically Human Resaource Quality, organizational commitment as well as reward and punishment system inderictly impact on HEI Performance via RbM implementation. It may be concluded that RbM implementation is much important to be realized then by increasing Human Resource Qualtiy, Organizatioinal Commitment as well as Reward and Punishment system are able to realize better HEI Performance.Theoretical contribution/Originality: This research is purposed to confirm goal setting theory related to RbM implementation in study context in HEI.Practitioner/Policy implication: This research result may become an input for HEI management to increase it performance via RbM policy implementation.Research limitation/Implication: This research may be executed in private HEI in eastern West Java.